Current trends in physical and physiological profile of elite WKF karate athletes: a systematic review - Eliza Gaweł; Miłosz Drozd; Adam Zając (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background This qualitative analysis aimed to: identify the physical and physiological factors that characterize elite WKF kumite and kata athletes, identify testing protocols that are used to examine the above mentioned profiles of WKF karatekas and indicate the variables that are significant for elite-level performance. Methods A search of electronic databases (PubMed, EBSCO, Scopus) was conducted to identify all studies on physical and physiological profile in elite karatekas from 2012 to 2024. A JBI Qualitative Data Extraction Tool for systematic reviews of qualitative evidence was fulfilled in order to determine which variables should be extracted. The quality of the included studies was assessed based on the JBI Critical Appraisal Checklist. Results 164 full-text articles were evaluated to determine eligibility, while 20 met the inclusion criteria and were subjected to detailed analysis, including risk of bias assessment. Finally, 17 full-text articles were included in the qualitative analysis. The following motor abilities and physiological components were evaluated by researchers: muscular strength (n = 8) muscular power (n = 11), speed (n = 8), agility (n = 6), flexibility (n = 6), aerobic metabolism (n = 9), anaerobic metabolism (n = 5). Conclusions The force-velocity characteristics with the dominant effect of the velocity component seem to be crucial in regard to performance outcomes in WKF karatekas. Moreover, elite karatekas are characterized by high flexibility of the hamstring muscles and well developed speed and agility abilities. The efficiency of aerobic and anaerobic metabolism is significant for high-performance in elite WKF kumite athletes, however aerobic capacity may be crucial. It is difficult to confirm the impact of the above mentioned energy systems on kata performance. Athlete’s age category and sex-related variables may affect the level of the analyzed motor abilities.